2021
DOI: 10.1016/j.jseint.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes and complications following distal biceps tendon reconstruction: a systematic review and meta-analysis

Abstract: Background Primary repair of chronic distal biceps tendon ruptures may not be possible because of tendon retraction, and there remains no clear consensus on the type of reconstruction technique used. The purpose of this study was to report the clinical outcomes and complication rates following reconstruction of chronic distal biceps tendon ruptures. Methods A systematic review was performed following PRISMA guidelines. The following databases were searched: Embase, MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…Avoid excessive retraction of lateral antebrachial cutaneous nerve, as this is a common postoperative nerve palsy 13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Avoid excessive retraction of lateral antebrachial cutaneous nerve, as this is a common postoperative nerve palsy 13 …”
Section: Discussionmentioning
confidence: 99%
“…Several techniques and graft choices have been described, with no method found to be superior to others to date. A recent meta-analysis by Litowski et al 13 compared autografts and allografts as well as graft fixation technique and found no difference in postoperative range of motion, strength, patientreported outcomes, or re-rupture rates. The autograft cohort had increased complications due to graft-site morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic distal biceps tendon ruptures are often associated with considerable retraction of the muscle-tendon unit, scarring, and tissue atrophy. Surgical reconstruction, in such situations, is not only technically demanding but also associated with higher complication rates [ 1 , 2 ]. Direct end-to-end repair may still be possible but requires a higher elbow flexion angle, which may result in postoperative failure or flexion contracture [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%